The Use of Neutrophil-to-Lymphocyte Ratio, Monocyte-to-Lymphocyte Ratio and Platelets-to-Lymphocyte Ratio in the Assessment of the Risk of Conversion and Complications After Cholecystectomy Performed Due to Symptomatic Cholelithiasis - Molasy B; Frydrych M; Kubala-Kukuś A; Głuszek S (Dove Medical Press, 2024)
Bartosz Molasy,1,2 Mateusz Frydrych,2 Aldona Kubala-Kukuś,3 Stanisław Głuszek1 1Collegium Medicum, The Jan Kochanowski University, Kielce, Poland; 2Department of General Surgery, St Alexander Hospital, Kielce, Poland; 3Institute of Physics, Jan Kochanowski University, Kielce, PolandCorrespondence: Bartosz Molasy, Department of General Surgery, St Alexander Hospital, Kościuszki 25, Kielce, 25-313, Poland, Tel +48 41 341 78 20, Email bartosz.molasy@onet.plPurpose: Laparoscopic cholecystectomy is quite a safe procedure, as only about 2% of cases result in clinically significant postoperative complications. The occurrence of conversion and postoperative complications is associated with prolonged hospitalization and higher perioperative mortality. Some parameters assessed in preoperative laboratory tests are used to predict the risk of conversion and clinically significant postoperative complications. The aim of this study was to evaluate the usefulness of preoperative neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR) and platelets-to-lymphocyte ratio (PLR) values in predicting the risk of conversion and complications in laparoscopic cholecystectomy performed due to symptomatic cholelithiasis.Patients and Methods: A retrospective analysis of patients operated on for symptomatic cholelithiasis was performed. The Results of preoperative laboratory tests were assessed - NLR, MLR and PLR. Their impact on early outcomes of surgical treatment was analyzed in the study population.Results: The analysis concerned 227 patients operated on for symptomatic cholelithiasis. The study group included 61 (26.9%) men and 166 (73.1%) women. As the NLR, MLR and PLR values increase, the length of hospitalization increases (rS 0.226, 0.247 and 0.181, respectively), as well as the risk of converting the procedure to an open method (p< 0.05). Moreover, with increasing NLR and MLR values, the grade of postoperative complications according to the Clavien-Dindo scale increases (p 0.0001 and 0.008, respectively). The grade of postoperative complications does not depend on the PLR value.Conclusion: The risk of conversion can be assessed based on preoperative NLR, MLR and PLR values in patients undergoing surgery for symptomatic cholelithiasis. Elevated preoperative NLR and MLR values are associated with a higher grade of postoperative complications in the Clavien-Dindo scale.Keywords: laparoscopic cholecystectomy, conversion, complications, neutrophil-to-lymphocyte ratio, monocyte-to-lymphocyte ratio, platelets-to-lymphocyte ratio